Cultural Determinants of Household Saving Behavior - Hannah Paule-Paludkiewicz; Nicola Fuchs-Schündeln; Paolo Masella (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze whether culture affects the saving behavior of households and which cultural channels matter for this household decision. To disentangle cultural effects from economic and institutional factors, we study how the saving behavior of second-generation immigrants relates to the attitudes and beliefs in the respective countries of origin. Using data from Germany and the UK, we find that culture significantly determines household saving behavior. The two cultural components that we robustly identify to affect saving rates are the attitudes towards thrift and the wealth accumulation motive: second-generation immigrants from countries that value thrift and wealth accumulation more tend to save more in Germany. By linking parents to their children, we present evidence that these attitudes are related to the saving behavior of both parents and children. We also provide evidence that future-orientation is related to the saving behavior through the intergenerational transmission of language, rather than the direct transmission of attitudes.
Keywords: D14; Z10; E21; 330